Early Detection of Depression Using the Zung Self-Rating Depression Scale - Colón, Luz N.; Guzmán-Yunqué, Francisco S.; Guevara-Ramos, Luz M. (Puerto Rico Health Sciences Journal, 2019)
see manuscript